Density by Design: Evaluating Transit Hubs for Transit-Oriented Development (TOD) in an Emerging Indonesian Metropolis - Haratama, Kusuma R.; Farizi, Ananda M. A.; Saputro, Maleakhi C.; Manggalasari, Lena C.; Thipphaya, Phitchayathida (Institute of Research and Community Outreach - Petra Christian University, 2026)
Rapid urbanization in Indonesian cities has increased interest in Transit-Oriented Development (TOD) as a strategy to promote compact, mixed-use, and transit-supportive urban forms. This study evaluates the TOD readiness of five major transit hubs in Surabaya—Purabaya Terminal, Joyoboyo Terminal, Gubeng Station, Surabaya Kota Station, and Pasar Turi Station—using a spatially explicit Built Environment Index (BEI). A Geographic Information System (GIS) approach was applied to analyze population density, employment density, land use mix, and accessibility within 400, 800, and 1,200 m service areas. These indicators were normalized and aggregated into the BEI under multiple weighting scenarios to reflect different planning priorities. The results identify Gubeng Station as the most TOD-ready hub, supported by high density, balanced job–to-population ratio, and strong land use integration, while Joyoboyo and Pasar Turi show limited TOD alignment. The proposed framework provides a replicable, data-driven tool to support TOD prioritization in emerging metropolitan contexts.